Research on the impact of multidimensional poverty in childhood on disability in middle-aged and older adult - Ruirui Xie; Fei Zhao; Lili Ding; Huiling Dong; Bingyi Wu (Frontiers in Public Health)
ObjectiveThis study measured the incidence of multidimensional poverty in childhood and decomposed the poverty index to explore the impact of multidimensional poverty in childhood on disability in middle-aged and older adult.MethodsThe A-F poverty double identification method was employed to assess children's multidimensional poverty, and in accordance with standard scientific research methods, its influence on the disability status of middle-aged and older adult was analyzed through Probit regression. Robustness testing was conducted using the propensity score matching method.Results(1) Multidimensional poverty in childhood increased the probability of disability among middle-aged and older adult by about 4.2%. (2) Heterogeneous results indicated that childhood multidimensional poverty had differential urban-rural impacts on the disability status of middle-aged and older adult (P < 0.05). (3) Multidimensional poverty in childhood had long-term negative consequences for both men and women, with significant adherence (P < 0.05). In contrast, the negative impact on women's health status was greater.ConclusionsChildren's needs vary across generations. In times of extreme resource scarcity, childhood poverty is primarily related to a lack of material resources. Multidimensional poverty in childhood affects the health status of middle-aged and older adult mainly through deprivation of material resources.